Bayesian feature selection in high‐dimensional regression in presence of correlated noise. Issue 1 (15th August 2014) - Feldman, Guy; Bhadra, Anindya; Kirshner, Sergey
Abstract : We consider the problem of feature selection in a high‐dimensional multiple predictors, multiple responses regression setting. Assuming that regression errors are i.i.d. when they are in fact dependent leads to inconsistent and inefficient feature estimates. We relax the i.i.d. assumption by allowing the errors to exhibit a tree‐structured dependence. This allows a Bayesian problem formulation with the error dependence structure treated as an auxiliary variable that can be integrated out analytically with the help of the matrix‐tree theorem. Mixing over trees results in a flexible technique for modelling the graphical structure for the regression errors. Furthermore, the analytic integration results in a collapsed Gibbs sampler for feature selection that is computationally efficient. Our approach offers significant performance gains over the competing methods in simulations, especially when the features themselves are correlated. In addition to comprehensive simulation studies, we apply our method to a high‐dimensional breast cancer data set to identify markers significantly associated with the disease. Copyright © 2014 John Wiley & Sons, Ltd.